Utilizing emotions for ethical decision making in leadership - Griffith, J.; Zeni, T.; Johnson, Genevieve (2014)
Modern organizational leaders must rise to the challenge of making both ethically sound decisions as well as traditional fiscal decisions in order to remain competitive in today’s marketplace. It is critical for leaders to be mindful of how emotions may assist or hinder them throughout the ethical decision-making process. Attempting to ignore the emotional component of ethical decision making or pretending that emotions do not exert influence on decisions is foolhardy and disregards both empirical and theoretical research suggesting otherwise. The challenge for leaders is how to best incorporate emotion into ethical decision making. This chapter examines several theoretical models of emotion and ethical decision making, applies theoretical and empirical findings to explain how two common emotions—anger and anxiety—impact ethical decision making, and provides recommendations for leaders seeking to improve ethical decision-making outcomes.